2012
DOI: 10.1016/j.foodcont.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of ochratoxin a and aflatoxins in chocolate marketed in Brazil

Abstract: a b s t r a c tThis study investigated the occurrence of aflatoxin B 1 , B 2 , G 1 and G 2 and ochratoxin A in chocolate marketed in Brazil. A hundred and twenty-five samples of powdered, bitter, dark, milk and white chocolate were evaluated for mycotoxins. Ochratoxin A was the most common mycotoxin in the evaluated samples, contaminating 98% of the purchased chocolate. A co-occurrence of aflatoxins was observed in 80% of all samples evaluated. The bitter, dark and powdered chocolate samples had the largest pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…The survey carried out on 42 samples of bitter chocolate in Japan [ 34 ] revealed 22 (52%) samples contaminated with mean a fl atoxin B1 concentrations of 0.18 m g/kg and a maximum of 0.6 m g/kg. A fl atoxin contamination was also reported by Copetti et al [ 31 ] when evaluating the co-occurrence of ochratoxin A and a fl atoxins in 125 samples of chocolate marketed in Brazil (powdered and bitter, dark, milk, and white bars, 25 samples each). The analyses revealed the co-occurrence of these two mycotoxins in 80% of the samples, with presence of a fl atoxins at mean levels of 0.53, 0.66, 0.43, 0.08, and 0.01 m g/kg in 96% of powdered, 100% of bitter, 100% of dark, 72% of milk, and 20% of white chocolate samples, respectively.…”
Section: A Fl Atoxins In Cocoa and Chocolatesupporting
confidence: 65%
“…The survey carried out on 42 samples of bitter chocolate in Japan [ 34 ] revealed 22 (52%) samples contaminated with mean a fl atoxin B1 concentrations of 0.18 m g/kg and a maximum of 0.6 m g/kg. A fl atoxin contamination was also reported by Copetti et al [ 31 ] when evaluating the co-occurrence of ochratoxin A and a fl atoxins in 125 samples of chocolate marketed in Brazil (powdered and bitter, dark, milk, and white bars, 25 samples each). The analyses revealed the co-occurrence of these two mycotoxins in 80% of the samples, with presence of a fl atoxins at mean levels of 0.53, 0.66, 0.43, 0.08, and 0.01 m g/kg in 96% of powdered, 100% of bitter, 100% of dark, 72% of milk, and 20% of white chocolate samples, respectively.…”
Section: A Fl Atoxins In Cocoa and Chocolatesupporting
confidence: 65%
“…The results obtained for OTA levels of cocoa powder samples in our study are similar to those reported in the literature. OTA has been detected in 92 to 100% of evaluated cocoa powder, with average levels between 0.18 and 7.8 µg/kg (Gilmour and Lindblom, 2008;Miraglia and Brera, 2002;Turcotte and Scott, 2011;Copetti et al, 2012). The prevalence of OTA reported in the literature for chocolate is also high [60 to 100% in chocolate (0.08 to 0.88 µg/kg)] (Gilmour and Lindblom 2008;Turcotte and Scott, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…The average was 0.64 ± 0.53 µg/kg for cocoa for export (grade I and II), and that for non-exportable cocoa (under grade) was 1.9 ± 1.9 µg/kg.Several authors reported that cocoa manufacturing operations reduce OTA content. The operations of roasting, shelling, and the addition of additives were identified as operations that may reduce OTA content by 90% (Copetti et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed aflatoxins in 80% of the examined samples. A strong relationship was observed between the occurrence of ochratoxigenic fungi and the ochratoxin A content in the chocolate samples [3,13,23]. One hundred and seventy-nine, out of the 300 samples analyzed, were positive for ochratoxin A contamination, representing 60% of the purchased products marketed in Italy [2].…”
Section: Mycotoxin Contents Of Localmentioning
confidence: 92%
“…Moreover, maximum limits of mycotoxins for all food products should be specifically established in the country. Publications are accessible with the mycotoxins contamination of chocolates in different realms [23] but not a single one from Pakistan.…”
Section: Mycotoxin Contents Of Localmentioning
confidence: 99%